Discovery of Recipes Based on Ingredients using Machine Learning - Samsudeen, M. Salomi; Kumar, R. Arun; Avinash, B.; Prabhu, A. Maria Santhosh (International Journal of Psychosocial Rehabilitation, 2020)
There are millions of recipes which are uploaded on websites. But still, the user cannot find what dishes can be cooked by using the ingredients the user has. A deep learning approach is focused on finding out the cuisine involved in a certain recipe through various ingredients used in it. Some ingredients have a unique feature which will be available only at a certain part of the country. A novel method is used to find out the best-suggested recipe through some available ingredients based on use. A common data set is created which consists of a global recipe and their procedure to cook it. A recipe is suggested as well as a web link to view the recipe procedure. A recommendation method is used in which the ingredients available by the user is taken as input and analyzation process is done with the help of data-set collected, and the appropriate dishes or recipes is recommended to the user by Machine Learning 9using K-Nearest Neighbors algorithm. The discovered output is visualized in the form of Website which is more convenient and user-friendly.